Fundamentals of fragrance chemistry - Sell, Charles S. (Wiley-VCH, 2019)
"This book provides chemists and chemists-to-be with everything they need to know in order to create welcome new fragrances for the wold to enjoy. It offers a simplified introduction into organic chemistry, including separation techniques and analytical methodologies; discusses the structure of perfume creation with respect to the many reactive ingredients in consumer products; and shows how to formulate effective and long-lasting scents. Fundamentals of Fragrance Chemistry starts by covering the structure of matter in order to show how its building blocks are held together. It continues with chapters that look at hydrocarbons and heteroatoms. A description of the three states of matter and how each can be converted into another is offered next, followed by coverage of separation and purification of materials. Other chapters examine acide/base reactions, oxidation and reduction reactions; perfume structure; the mechanism of olfaction; natural and synthetic fragrance ingredients; and much more"--Page 4 of cover.